Lawrence in Arabia : war, deceit, imperial folly and the making of the modern Middle East - Anderson, Scott, 1959- (Doubleday, 2013)
A narrative chronicle of World War I's Arab Revolt explores the pivotal roles of a small group of adventurers and low-level officers who orchestrated a secret effort to control the Middle East, demonstrating how they instigated jihad against British forces, built an elaborate intelligence ring and forged ties to gain valuable oil concessions.